1982
DOI: 10.1139/v82-308
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical photodimerization of 7-acetoxycoumarin: the acetoxy group as a steering agent

Abstract: Among the various substituted coumarins investigated only 7-acetoxycoumarin is observed to photodimerize topochemically in the crystalline state and this observation may be of importance in the context of "crystal engineering".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 3 publications
2
10
0
1
Order By: Relevance
“…The other four substituents interact through the 3E'(b) orbital and this interaction will increase the bond length C(1)-C(2). The observed bond length C(1)-C(2), 1.557 (5)/k, agrees well with bond lengths found in similar compounds: ethyl 1,2, 2 -tricyano -3,3 -dimethylcyclopropane-1 -c arboxylate, 1.552 (3)/~ (Ramasubbu, Rajaram & Venkatesan, 1982); ethylenetetracarbonitrile, 1.559 (2)/k (Lemley, Skarstad & Hughes, 1976); 3-(2-methoxyphenyl)cyclopropane-l,l,2,2-tetracarbonitrile, 1.557 (3)/k (Usha & Venkatesan, 1980). If the nitrophenyl group had also been interacting, then the bond length C(1)-C(2) would be significantly shorter than 1.557 (5)/k.…”
Section: Cish10n404supporting
confidence: 88%
See 2 more Smart Citations
“…The other four substituents interact through the 3E'(b) orbital and this interaction will increase the bond length C(1)-C(2). The observed bond length C(1)-C(2), 1.557 (5)/k, agrees well with bond lengths found in similar compounds: ethyl 1,2, 2 -tricyano -3,3 -dimethylcyclopropane-1 -c arboxylate, 1.552 (3)/~ (Ramasubbu, Rajaram & Venkatesan, 1982); ethylenetetracarbonitrile, 1.559 (2)/k (Lemley, Skarstad & Hughes, 1976); 3-(2-methoxyphenyl)cyclopropane-l,l,2,2-tetracarbonitrile, 1.557 (3)/k (Usha & Venkatesan, 1980). If the nitrophenyl group had also been interacting, then the bond length C(1)-C(2) would be significantly shorter than 1.557 (5)/k.…”
Section: Cish10n404supporting
confidence: 88%
“…Particularly noteworthy is the distance O(4)...C(5) which is as short as 2.83/k. Such interactions have also been found in the crystal structures of BrC(CN) 3, C1C(CN) 3, CHaC(CN) 3 (Witt et al, 1972), tetrahydroxy-p-benzoquinone (Klug, 1965), and ethyl 1,2,2-tricyano-3,3-dimethylcy clopropane-1 -carboxylate (Ramasubbu et al, 1982).…”
Section: Cish10n404mentioning
confidence: 52%
See 1 more Smart Citation
“…(12) 498 (I) -339 (7) 41 (2) 934 (12) 368 (1) -2320 (7) 42 (2) 470 (13) 555 (1) -4121 (7) 40 (2) 1644 (11) 1120 (1) --5944 (6) 37 (1) 3301 (11) 1442 (1) -5778 (6) 35 (1) 5453 (12) 1563 (1) --3880 (7) 40 (2) 5879 (12) 1351 (I) -2084 (7) 40 (2) 4205 (1 l) 1026 (1) -2238 (6) 35 (1) 2083 (ll) 902 (1) -4136 (6) 33 (I) 3707 (9) 352 (1) 1377 (5) 59 (1) 2973 (8) 1646 (1) --7648 (4) 42 (1) 1644 (12) 1981 (1) -7684 (7) 41 (2) 552 (9) 2102 (I) -6257 (6) 60 (1) 1739 (20) 2166 (2) -9687 (10) 59 (2) Geometry of the molecule. Bond lengths and angles in 6-acetoxycoumarin are in good agreement, within experimental error, with those observed in 7-acetoxycoumarin (Ramasubbu et al, 1982). The plane of the acetoxy group makes a dihedral angle of 60.9 (5) ° with the plane of the coumarin ring, whereas in 7-acetoxycoumarin this angle is 57.4 (3) °.…”
supporting
confidence: 79%
“…An analysis of the reactivity pattern of these compounds revealed that chloro and acetoxy groups are outstanding in their steering abilities; all the five chlorocoumarins investigated were photoreactive, while three (6-acetoxy-, 7-acetoxy-and 4-methyl-7-acetoxycoumarin) out of five acetoxycoumarins investigated dimerized upon irradiation yielding syn head-head dimers. The crystal structure of 7-acetoxycoumarin (Ramasubbu, Gnanaguru, Venkatesan & Ramamurthy, 1982) 0108-2701/88/020307-05503.00 revealed that the reactive molecules pack with the reactive double bonds separated by 3.833 (2)/~, along the a axis. To investigate further the details of the molecular packing of the other acetoxycoumarins, crystallographic investigations of 6-acetoxy-and 4-methyl-7-acetoxycoumarins were undertaken.…”
mentioning
confidence: 99%